Strongyloides stercoralis is associated with significant morbidity in rural Cambodia, including stunting in children. - Armelle Forrer; Virak Khieu; Fabian Schär; Jan Hattendorf; Hanspeter Marti; Andreas Neumayr; Meng Chuor Char; Christoph Hatz; Sinuon Muth; Peter Odermatt (Public Library of Science (PLoS), 2017)
Strongyloides stercoralis is a soil-transmitted nematode that can replicate within its host, leading to long-lasting and potentially fatal infections. It is ubiquitous and highly prevalent in Cambodia. The extent of morbidity associated with S. stercoralis infection is difficult to assess due to the broad spectrum of symptoms and, thus, remains uncertain.Clinical signs were compared among S. stercoralis infected vs. non-infected participants in a cross-sectional survey conducted in 2012 in eight villages of Northern Cambodia, and before and after treatment with a single oral dose of ivermectin (200μg/kg BW) among participants harboring S. stercoralis. Growth retardation among schoolchildren and adolescents was assessed using height-for-age and thinness using body mass index-for-age. S. stercoralis prevalence was 31.1% among 2,744 participants. Urticaria (55% vs. 47%, OR: 1.4, 95% CI: 1.1-1.6) and itching (52% vs. 48%, OR: 1.2, 95% CI: 1.0-1.4) were more frequently reported by infected participants. Gastrointestinal, dermatological, and respiratory symptoms were less prevalent in 103 mono-infected participants after treatment. Urticaria (66% vs. 11%, OR: 0.03, 95% CI: 0.01-0.1) and abdominal pain (81 vs. 27%, OR: 0.07, 95% CI: 0.02-0.2) mostly resolved by treatment. S. stercoralis infection was associated with stunting, with 2.5-fold higher odds in case of heavy infection.The morbidity associated with S. stercoralis confirmed the importance of gastrointestinal and dermatological symptoms unrelated to parasite load, and long-term chronic effects when associated with malnutrition. The combination of high prevalence and morbidity calls for the integration of S. stercoralis into ongoing STH control measures in Cambodia.